(untitled) (Plant Tissue Culture and Biotechnology, 2022)
Disinfected mature seed embryos of Picralima nitida, were cultured in MS medium supplemented with different concentrations and combinations of 2,4-D, BAP and NAA to determine an efficient protocol for in vitro propagation. Nine culture media made of combination of different components were used in a factorial design with three replications. Results showed up to 80 ± 4% disinfection rate with combination of triton x- 100 (0.2%) and sodium hypochlorite (30%). Embryo germination was highest on control medium. Rooting was higher (2±1 roots per embryo) after 4 weeks on control medium and on BAP supplemented medium at 0.8 μM while the longest root (1.5±0.5 cm) was observed on 2,4-D supplemented medium at 1.8 μM. Black soil was suitable for leaf formation (4 ± 2 leaves) and shoot elongation (2±1 cm) after 8 weeks in acclimatisation. These results show efficient disinfection, regeneration and acclimatisation of Picralima nitida. Plant Tissue Cult. & Biotech. 31(2): 143-151, 2021 (December)